Representation of the Native Africans: A Postcolonial Reading of Joseph Conrad’s Heart of Darkness - Sultana, Humaera; Ahmed, Ilias; Shariful Islam, Md. (Journal of History Culture and Art Research, 2024)
Abstract This article essentially examines Joseph Conrad’s presentation of the native Africans as black, savage, barbarous, primitive, shadow of evil, unproductive, and inhuman in his famous novella Heart of Darkness (1899). The paper sets out focusing on the facts related to the postcolonial studies that have become a new academic discipline which criticizes those systems created by the colonizers. Postcolonial theory participates in discussing race, othering, subaltern, and orientalism. The word 'postcolonial' pertains to the repercussions of imperialism or colonialism on various cultures and communities. Although there have been many discussions on the theme of exploitation of Africa by the colonizers in Heart of Darkness (1899), the present study explores and explains how Conrad is unsympathetic in depicting the identity and life style of the native Africans and backwardness of this region through the qualitative research by using many postcolonial terms like racism, othering, subalternity, and orientalism. The findings of the experiment demonstrate an amplification of the Europeans' perception of the orient as distinct and lacking in civilization. Consequently, it is argued that it becomes incumbent upon the Western world to pass judgement on them. However, it is paradoxical that the individuals shown as seemingly civilised in the book are, in fact, quite savage. Indeed, the insatiable desire for power, feelings of envy, and the relentless pursuit of ivory have propelled these individuals towards a detestable transformation, whereby they have become corrupt, horrible, and ruthless entities that exploit the indigenous Africans as enslaved labourers for their own self-serving objectives, then discarding them as if they were disposable refuse.